Cyanobacterium Spirulina platensis LUQS1: effects on serum lipids and kidney in domestic cats, Felis catus - Lokman Shamsudin; Syarifah Ab Rashid; Nur Nabila Mohd Rozaini; Than Kyaw
Aims: Researchers found a wide range of therapeutic properties in Spirulina sp. including as anti-cholesterol or antihyperlipidemic agent. In this study, the lipid levels of domestic F. catus were induced in order to scrutinize the antihyperlipidemic effects of local S. platensis LUQS1 strain, specifically at concentrations of 0.5 g/day and 1.0 g/day. Methodology and results: Elevation of serum lipid levels viz. total cholesterol (TC), high density lipoprotein (HDL), low density lipoprotein (LDL) and triglycerides (TG) as well as the status of kidney [creatinine (Cr) and blood urea nitrogen (BUN)] were observed in four groups of F. catus for 45 days. The highest levels for TC, LDL and TG (P < 0.05) were recorded in high cholesterol diet group (CD) at day 45 with 291.67±2.87 mg·dL⁻¹, 111.60±9.73 mg·dL⁻¹ and 146.33±10.44 mg·dL⁻¹, respectively. HDL levels in Spirulina-treated groups (CA and CAA) were better than normolipidemic group (control, SD group), of which the maximum levels were displayed at day 30 specifically 72.87±6.08 mg·dL⁻¹ by cats-fed with high cholesterol diet treated with 0.5 g/day S. platensis LUQS1 (CA group). There were insignificant differences (P > 0.05) in the BUN levels; however, the Cr levels in CAA group (day 30 and 45) were slightly out of normal range but did not classify under chronic condition. Conclusion, significance and impact of the study: Alternative treatments on hyperlipidemic cats were rarely reported by researchers and medicinal practitioners. Thus, the findings of this present study provided a genuine knowledge concerning the lipid-lowering effect of S. platensis LUQS1 on the hyperlipidemic cats.